Apoptosis‐inducing and Antitumor Activity of Neolignans Isolated from Magnolia officinalis in HeLa Cancer Cells. (28th November 2012) - Youn, Ui Joung; Fatima, Nighat; Chen, Quan Cheng; Chae, Sungwook; Hung, Tran Manh; Min, Byung‐Sun
Abstract : Two neolignans, 4′‐methoxymagndialdehyde (1) and magnaldehyde B (2), were isolated from the stem bark of Magnolia officinalis (Magnoliaceae), evaluated for apoptosis‐inducing effects in human cervical epitheloid carcinoma HeLa cells. The apoptosis‐inducing activity of compounds 1 and 2 were assessed by DNA content using flow cytometric analysis. In the immunoblotting analysis, the treatment with 1 and 2 resulted in the cleavage of procaspase‐8 and ‐3 and poly(ADP‐ribose)polymerase into active forms. In addition, in vivo, the administration of 2 to Lewis lung carcinoma‐inoculated mice evidenced a significant inhibition of tumor growth (volume) with reduction of 28.7% at concentration of 20 mg/kg, as compared with the control mice. These findings suggest that 2 can inhibit the proliferation of tumor cells, and might be an anti‐tumoric agent. Copyright © 2012 John Wiley & Sons, Ltd.